A Rare Anatomical Variation: A Case of a Common Celiacomesenteric Trunk in a Cat. (29th May 2013) - Gorissen, B. M. C.; Moens, H. C.; Wolschrijn, C. F.
Summary In this study, we present a cat with a common 1‐cm‐long celiacomesenteric trunk. The arteria hepatica branched off first from the separate arteria celiaca and gave rise to the arteria gastrica dextra and arteria gastroduodenalis. The main stem of the arteria celiaca then split into the arteria gastrica sinistra and the arteria lienalis. The arteria mesenterica cranialis extended ventrocaudally in the mesentery. This variation is due to developmental changes in the ventral splanchnic arteries, and they are quite varied. The basic architecture and perfused organs are comparable, which indicates that the presence of a common celiacomesenteric trunk is more related to individual development than to phylogeny or function.